Analisis Biaya Pemeliharaan Aktiva Tetap (Mesin) untuk Menjaga Kelancaran Produksi pada CV Rabbani Kota Medan - Faisal Akbar; Nurlaila Nurlaila; Nurul Jannah (Departement of Mathematics Education, 2023)
This study has a purpose to determine the budget for the maintenance of fixed assets (machines), to find out the realization of the budget for maintaining fixed assets (machines) is greater than the budget for maintenance costs, and to determine the effect of maintenance costs on fixed assets (machines) on the smooth production of CV Rabbani. The data analysis method used is descriptive test analysis technique, descriptive test is a way of formulating and interpreting existing data so as to provide a clear picture through collecting, compiling and analyzing data, so that a general description of the maintenance activities carried out by the company can be known. The results of the research that have been obtained explain that the decrease in the amount of production occurs due to the number of machines that are damaged so that it increases the amount of maintenance costs that exceed the total maintenance cost budget that has been set by CV Rabbani.